Hubungan Antara Diastasis Musculus Rectus Abdominis Dengan Involusi Uteri Postpartum Pervaginam (Fisioterapi : Jurnal Ilmiah Fisioterapi, 2009)
Background : During labour, depend on two powers (force) they are: a) the first power is produced involuntary by contractions muscle of uterus; and the second power (force) is voluntary contractions from abdominalis muscles. Objectives : the purpose of this study was to detect: 1) the correlation between diastasis of rectus abdominis muscle and involution of uterus at vaginal postpartum; 2) the average differences between diastasis of rectus abdominis muscle at primiphara and multiphara in vaginal postpartum. Method: This study is survey with crosssectional method. Kind of analysis is assosiatif between variable diastasis of rectus abdominis muscle and involution of uterus at vaginal postpartum; and comparative analysis between distasis of rectus abdominis muscle at primiphara and multiphara. Technique of data analysis: 1) Test of the rule data analysis sample with normality test; 2) Hypothesis test: a) assosiatif analysis with Pearson product moment statistic; b) t-test  two samples independent. Results: 1) The correlation between diastasis of rectus abdominis muscle and involution of uterus for  2 -24 hours vaginal postpartum placenta are significant; with coefficient correlation product moment is 0,646, and the result of t-stat is 3,489; that more than t-critic α 0,05 df 36 = 2,03; 2). Statisticaly be found the average differences are significant between diastasis of rectus abdominis muscle at primiphara and multiphara for 2 -24 hours in vaginal postpartum placenta. On the test analysis got t-stat = 3,032. While t-critic with α = 0,05 and df = 17 is 2,11; thus, t-stat (= -2,929) > t-critic (=2,11). The average size of diastasis rectus abdominis muscle in   primiphara = 54,78 mm, and in  multiphara = 61,70 mm.Keywords : Diastasis of Rectus Abdominis Muscle, Involution of uterus, Core  Integrity